2021
DOI: 10.3390/medicina58010062
|View full text |Cite
|
Sign up to set email alerts
|

Bispectral Index Monitoring and Observer Rating Scale Correlate with Dreaming during Propofol Anesthesia for Gastrointestinal Endoscopies

Abstract: Background and objectives: Dreaming is a commonly reported side effect of propofol anesthesia. Materials and Methods: We investigated the inci-dence and character of dreams in patients undergoing intravenous propofol anesthesia and cor-related it with an observer rating scale of facial expression on the seven-point scale from pain to smile. A total of 124 patients undergoing gastrointestinal endoscopy were recruited in the pro-spective observational study. Bispectral index (BIS), blood pressure (BP), and pulse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…14,16 Propofol induced dreaming was reported to be related to anesthetics, depth of anesthesia, age, gender, preoperative psychological state and other factors. [6][7][8][9][10] However, the baseline information of our study was comparable among the groups. Matus et al 8 found that the Bispectral Index value of dreamers at 2 min after endoscopy initiation was lower than that of non-dreamers.…”
Section: Discussionmentioning
confidence: 77%
“…14,16 Propofol induced dreaming was reported to be related to anesthetics, depth of anesthesia, age, gender, preoperative psychological state and other factors. [6][7][8][9][10] However, the baseline information of our study was comparable among the groups. Matus et al 8 found that the Bispectral Index value of dreamers at 2 min after endoscopy initiation was lower than that of non-dreamers.…”
Section: Discussionmentioning
confidence: 77%
“…Xu et al [20] observed that among the dreamers, approximately one-third reported pleasant dreams. Studies have demonstrated that the main factors influencing dreams during anesthesia include the kind and dosage of anesthetics, depth of anesthesia, sex, and preoperative psychological pretreatment [4,5,[20][21][22][23]. Furthermore, Yoshida et al [24] found that a less than 11 depression score of the HADS was highly correlated with positive dreams.…”
Section: Discussionmentioning
confidence: 99%
“…This includes monitoring the level of consciousness, an adequate visual examination of the patient, and monitoring the patient’s breathing and circulation [ 64 ]. One of the methods, which has often been used to assess the depth of sedation, especially when using propofol during endoscopies, is monitoring the bispectral index (BIS) [ 65 ].…”
Section: Monitored Anesthesia Care For Gastrointestinal Endoscopymentioning
confidence: 99%
“…BIS monitoring is a non-invasive method that processes EEG information, thus enabling measurement of the patient’s level of consciousness and depth of sedation. By using BIS monitoring, it is possible to reduce the applied dose of the drug, and the risk of too deep sedation, especially in elderly patients [ 65 , 66 , 67 , 68 ]. Considering the great heterogeneity of the conducted studies related to the use of BIS monitoring, other studies did not establish a specific clinical benefit that would include more adequate and improved oxygenation of patients, and a reduction in the risk of respiratory and circulatory complications [ 69 , 70 , 71 ].…”
Section: Monitored Anesthesia Care For Gastrointestinal Endoscopymentioning
confidence: 99%